Development of a test geometry for evaluating the hydrogen cracking susceptibility of high strength GMA welding consumables - Barbosa, P. M. R. (Cranfield University, 2002)
This thesis presents the work developed at Cranfield University through a research programme on the hydrogen cracking susceptibility of multipass girth welds of X-100 steel pipeline produced by the gas metal arc welding process (GMAW). The work aimed to develop a test geometry able to test very low hydrogen content GMAW consumables available in the market. A number of weldability' tests were studied and the Welding Institute of Canada Test (WIC) was selected as the initial configuration to be adjusted because of its simplicity and proved correlation of its results and field data in the past. A simplified one dimensional model of intensity of restraint was derived and the influence of the main geometrical parameters on the intensity of restraint was studied. The restraint length and the sectional area of the restraint plates combined with different groove preparations were employed to achieve four test configurations of successively increased severity. One particular configuration proved to generate hydrogen cracks and discriminated between the two consumables tested. Another configuration achieved to induce hydrogen and solidification cracks but was considered too much severe as it did not discriminate between those consumables. Additional adjustment of restraint length and the cross sectional area of the restraint plates in the plane perpendicular to the weld direction were performed. An optimal configuration prevented the occurrence of longitudinal cracking and induced transverse cracks typical of pipeline girth welding. This work studied a range of heat input from 0.3 to 0.6 kJ/mm. It was found that minimum values of heat input were not always the most critical for hydrogen cracking. It is suggested that there may be significant differences in the residual stress (as a result of the weld heat input) and that these stresses also influence the onset of cracking. The optimal configuration obtained was sensitive to consumables of very low hydrogen content and discriminated between the consumables tested. In order the test configuration can be validated, further tests are needed covering a wider range of consumables.